Self-organization patterns in electroluminescence of bistable ZnS:Mn thin-film structures - Vlasenko, N.A.; Purwins, H.-G.; Denisova, Z.L.; Kononets, Ya.F.; Niedernostheide, F.-J.; Veligura, L.I.; Zuccaro, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
An overview of recent original results concerning self-organized pattern formation in the emission of bistable alternating current ZnS:Mn thin - film electroluminescent structures (TFELS) as a dissipative system is given. The influence of technological factors, affecting the properties TFELS, and driving conditions on both the patterns and the hysteresis of the charge- voltage dependence that is responsible for bistability of the TFELS are considered. The correlation between patterns and the shape of the hysteresis is analyzed. The physical processes with positive and negative feedback, which serve, respectively, as activator and inhibitor in the given dissipative system, are discussed.